Facing a dilemma in the treatment of an internal mammary artery mycotic pseudoaneurysm: coil embolization or surgery? A case report and brief literature review. Issue 8 (26th August 2020) - Spiliopoulos, Kyriakos; Magouliotis, Dimitrios E; Spanos, Konstantinos; Salemis, Nikolaos S; Tsantsaridou, Angeliki; Karagiorgas, Georgios; Giannoukas, Athanasios D; Rountas, Christos
Abstract: While aneurysms of the internal mammary artery (IMA) complicate occasionally surgical procedures employing median sternotomy, or are associated with direct thoracic trauma, mycotic pseudoaneurysms of the vessel are rarely reported in the literature. We herein report a case of a 22-year-old man who developed a mycotic internal mammary artery pseudoaneurysm secondary to staphylococcal chest wall abscesses and was effectively treated by coil embolization. Additionally, the report provides a brief review focusing on the current state of treatment options for internal mammary artery aneurysms.